Faith Activities in the Home Scale A Validity and Reliability Study in Turkey - Özbay, Ahmet (2024)
The main purpose of this study is to adapt both the reliability and validity of the Faith Activities in the Home Scale into Turkish. Among the 355 university students, 190 female and 165 male students participated in this study, which was conducted using data obtained from Sakarya University students. The Faith Activities in the Home Scale are evaluated in two different aspects: importance and frequency. The fit indices obtained in confirmatory factor analysis according to frequency scoring (x2 = 65.50, SD = 21, RMSEA = 0.076, NFI = 0.92, NNFI = 0.90, IFI = 0.94, CFI = 0.94, RFI = 0.87, GFI = 0.96, AGFI = 0.92, SRMR = 0.046) and good fit indices (x2 = 56.31, SD = 21, RMSEA = 0.068, NFI = 0.95, NNFI = 0.95, IFI = 0.97, CFI = 0.97, RFI = 0.92, GFI = 0.97, AGFI = 0.93, SRMR = 0.042) obtained from confirmatory factor analysis according to importance scoring. The internal consistency reliability coefficient of the Faith Activities in the Home Scale for frequency scoring was 0.81, and the internal consistency reliability coefficient for importance scoring was 0.84. The corrected item-total correlation coefficients of the scale ranged between 0.41 and 0.55 for frequency scoring and between 0.36 and 0.63 for importance scoring. These findings imply that the Turkish version of the Faith Activities in the Home Scale can be considered a valid and reliable measurement tool that can be used in research.
Keywords: Confirmatory Factor Analysis; Faith Activities in the Home; Reliability; Validity